Taisnīguma izpausme bērnu tiesībās - Miezītis, Andis (Latvijas Universitāte, 2006)
A concept of justice in children’s rights can manifest oneself in various ways. Children’s favor is prior in comparison with adult rights, which, certainly means a reasonable restrictions. In several places there is stated by the law, that children’s rights must be restricted. The necessity of restricting ones rights is caused by two reasons: 1) person’s activity is the main cause of other person’s violation of rights; 2) person deliberately or unawares causes harm towards oneself. It is obvious that merely restricting ones rights or opposite – privilege someone, does not automatically bring justice. Thereby, concept of justice in contrast with such concepts as law and rights attains an abstract form. In contradistinction to last two concepts, the interpretation of justice might sound in diverse contexts, for it is evident none the same thing is just for all. Justice in children’s rights is related to, whether they have a chance to enjoy the very least of things their foregoers did, and develop it through nurture and education, moreover it must consider when interests of children and adults collide in democratic republic, children’s interests are prior, though mainly not for children lack of legal capacity, but because of their inability of protecting their choices, which however lies on parents.
Disclosure of Justice in the Rights of Children
Keywords: Tiesības